A revision of chromosome II (CD) mapping in Chironomus plumosus (Linnaeus, 1758) group (Diptera, Chironomidae) - Golygina, Veronika V. (Pensoft Publishers, 2012)
Abstract. A revision of the main and alternative banding sequences in chromosome II (CD) has been made for all 14 species of the Chironomus plumosus (Linnaeus, 1758)group. A new version of mapping has been suggested for 10 out of 18 banding sequences of arm C and 12 out of 22 banding sequences of arm D. Mapping of 7 banding sequences has been done for the first time according to the Keyl-Devai system. Phylogenetic relationships of banding sequences of chromosome II have been discussed.